The role of selective contacts and built-in field for charge separation and transport in photoelectrochemical devices. Issue 16 (30th June 2022) - Schleuning, Markus; Ahmet, Ibbi Y.; van de Krol, Roel; May, Matthias M.
Abstract : The principal driving force for charge carrier separation in a PEC cell is given by the QFL gradients. Upon illumination the E-field is reduced by the amount of photovoltage delivered. Selective contacts are thus decisive for device performance. Abstract : Direct photoelectrochemical (PEC) solar water splitting has the potential to be a key element in a sustainable energy supply chain. However, integrated PEC systems based on metal oxides still lack the high efficiencies required for large-scale, economically feasible applications. A main obstacle for the realization of higher solar-to-hydrogen efficiencies is the appropriate design of the semiconductor–catalyst and semiconductor–electrolyte interfaces. Thus, a more accurate understanding of the energy loss mechanisms and the driving forces that determine the charge separation, transport and recombination of electrons and holes in a PEC device would be instrumental for the selection of the most appropriate design routes. In this context we highlight a common misconception within the PEC research community, which is to consider the built-in electrical field at the solid/liquid interface as essential for charge separation. We subsequently emphasize the established viewpoint within the photovoltaic research community that the gradient of the electrochemical potential is the principle driving force for charge separation and efficient solar energy conversion. Based on this realization, we argue that improved contact design in PEC devices should be one of the main research directions in the design of PEC devices. To address this challenge, we take a closer look at how optimized contacts have been constructed so far and present potential design approaches which can be used to further improve the performance of PEC devices.